COMMUNICATIONS COMMITTEE PRESENTATION ON THE PUBLIC SMOKING ISSUE (Tufts Archival Research Center, 2007)
Confidential; Communications Committee report on Public Smoking. Refers to the ETS issue as the most difficult one for the tobacco industry. Mentions the constant battle with anti-smokers and their efforts to change existing systems. States that only 17 states and 300 localities out of more than 30,000 jurisdictions require businesses to restrict smoking and reports that the rest of the companies voluntarily choose to restrict smoking as well. Addresses the issue of discrimination against smokers and workers who chose to smoke.